From Denationalisation to Wholesale Broadband Access: A Retrospective of Regulatory Policies in the UK for the Communications Industry. Issue 3 (September 2014) - Deshpande, Advait; Jones, Allan
This paper examines the shifting regulatory policies in the United Kingdom (UK) across three market segments, telecommunications, radio/television and cable, starting with British Telecom's (BT's) denationalisation in 1984. For the period examined, this paper focuses on following key events – – The phased liberalisation of the UK communications industry starting with the BT-Mercury Communications duopoly in 1984 – The allocation of cable franchises as regional monopolies in the mid-1980s – Introduction of satellite broadcasting and the influence of British Sky Broadcasting (BSkyB) Corp. on broadcasting services in the 1990s – The emergence of the Internet/Web and the subsequent development of a broadband policy from mid-1990s onwards Drawing on Dodgson et al.'s concepts of Market logic, Coordination Logic, and Complex-Evolutionary Logic, the authors argue that the forms of regulation introduced shaped the ways the UK communications industry developed. Thus although the denationalisation grew out of a free market ideology, in practice the free market philosophy was tempered for a number of pragmatic reasons. Prominent among these was a need to create a competitive market in a context where competitors would be unlikely to emerge without regulatory intervention, and an emphasis on price competitiveness to ensure that the end-users benefitted from the best possible prices on available products and services. Subsequent events show that these interventions had unintended consequences. The unforeseen popular demand for Internet/Web access found regulators struggling to find ways to promote a competitive market, and incumbent operators struggling to find a way to offer a suitable product.